Analisis Penerapan Metode Pencatatan Terhadap Persediaan Barang Dagang Benang Pada PT. Mitra Bangun Cemerlang (MBC) Tahun 2022 - andy Januar Permana; Rasyiddin, Ahmad; Eliana rosaliana; Hurian Kamela (Universitas Tangerang Raya, 2022)
Inventories are part of current assets and also one of the means to carry out company activities needed by various types of companies such as trading, manufacturing and service companies. Recording is a way of working or a process system for recording or writing (in and out) of a transaction activity in a complete notebook. Meanwhile, the recording method has the goal of facilitating the implementation of an activity in determining or achieving a certain goal. PT. Mitra Bangun Cemerlang (MBC) is engaged in the textile sector. This research focuses on recording the inventory of yarn merchandise. The researcher wants to examine how